Habitual visual acuity and visual acuity threshold demands in Nigerian school classrooms - Onyekachukwu Mary-Anne Amiebenomo; Ejitu Mfon Isong; Mark Eghaghe Edosa; Joy Margaret Woodhouse (Scientific Reports, 2022)
Abstract This study was designed to estimate the burden of blindness and vision impairment in school children, and to determine the proportion of students meeting the visual acuity (VA) demand for their classrooms. From 148 primary and secondary school classrooms in Edo State, Nigeria, the habitual distance and near VA of over 2000 students were measured. Values obtained were compared with the calculated distance VA demand and actual near VA demand for their classrooms. Measures used to calculate the VA demand were working distance and smallest text size on learning materials, at both distance and near. We also determined the relationship between age and calculated VA demand and the effect of factors such as school ownership and school type on the VA  demand. Habitual distance vision impairment was found in 0.8% of pupils, including 2 (0.10%) who met the WHO criteria for blindness. The average VA demand at the furthest and nearest sitting position to the board was 0.21 ± 0.23 and 0.65 ± 0.33LogMAR, respectively. Near working distance of students ranged from 15.00 to 37.20 cm, and the near VA demand as well as actual near VA demand (using a 2.5 times acuity reserve) was 0.60 ± 0.17 and 0.20 ± 1.7LogMAR, respectively. LogMAR VA demand increased (size of print decreases) with increasing age, at both distance (r =  − 0.549, p = 0.070) and near (r =  − 0.921, p < 0.0001). The VA demand at maximum distance and the actual near VA demand differed significantly by school ownership and between primary and secondary schools. Most students had VA better, but up to 11% of students per class had VA poorer than their classroom demands. Although the majority of students had better VA than their classroom demands, for students with reduced vision, learning could be negatively impacted. It is important to continually screen students for vision impairment and ensure prompt referral and treatment. These findings have implications for managing vision problems in children, as well as enabling appropriate classroom arrangements for those with vision impairment.